A federation of Europe : the Interlaken plan for action for a European assembly to be convened forthwith to draft a constitution for the United States of Europe adopted by the European Parliamentary Union on the 4th September, 1948. (London : St. Clements Press, 1948)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Europese eenmaking